Avaliação auditiva em crianças de 7 a 9 anos com e sem IRDA ao nascimento atendidas em um serviço de referência de triagem auditiva neonatal - Juliana Brito Borges (2018)
The present study presents the objective of evaluating the hearing of children aged 7 to 9 years with and without risk indicators for hearing loss at birth attended at a referral service in Belo Horizonte, Minas Gerais. It is a scientific production that integrates the project "DANPE- Progressive Neurosensory Hearing Loss in Childhood: Monitoring, diagnosis and technological development". We considered as some sample children who underwent Universal Neonatal Hearing Screening between January 2009 and December 2009 with a total of 144 children. The level of significance was set at 5% (p≤0.05). Statistical significance was considered as a significant trend at the level of 10% (p ≤ 0.10) in the evaluation in which 72 had at least one indicator of risk for hearing loss and the other 72 children with no risk indicator for hearing loss hearing loss, formed the study control group. Unilateral sensorineural hearing loss was detected by means of pure tone audiometry in 1.4% in relation to the 72 children evaluated with a risk indicator for Hearing Impairment. Tinnitus audiometry was adequate for 99.3% of the children evaluated (total of 144 individuals). The group at risk for hearing impairment is 3,828 times more likely to present an inadequate Simplified auditory processing evaluation (ASPA) result compared to the non-hearing-impaired group. The group at risk for hearing impairment is 5,068 times more likely to present a complaint of difficulty in school compared to the group without risk of hearing loss. In the group with risk for hearing loss, individuals with complaints of school difficulties are 20,357 times more likely to present inadequate ASPA when compared to individuals who have no complaints of school difficulties. It was possible to conclude that the auditory evaluation should be carried out the tests of immittance, pure tone audiometry, ASPA and if possible auditory brainstem potential (BAEP), with the purpose of doing a preventive work, performing auditory preservation strategies , so that these patients have a better quality of life and subsequently a decrease in the sequelae related to hearing loss in preschool and school children.